(untitled) (Weinheim, 2000)
The book focuses on structural and property characterization of nanocrystals and their assemblies, with an emphasis on basic physical approach, detailed techniques, data interpretation and applications." "Intended as a comprehensive reference work for postgraduate students and researchers in the field who are specialized in materials chemistry, materials physics, and materials science
Keywords: Vật liệu cấu trúc nano,Nanostructured materials